Affective Features of Linguistic Attitudes of College Students - López Gil, Karen S.; Chamorro Mejía, Mónica (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper describes the affective features of the linguistic attitudes of students from different geolectal areas of Colombia who attend to a university in Cali. This city is characterized by its cultural and dialectal plurality, partly due to forced migrations from armed conflict areas. In addition, in recent years, the Colombian State has boosted the access of top students to the university, mostly from rural areas. The diversity of uses of the language that students have built in their home contexts could get in tension with the dynamics of the college environment. From a mentalist perspective in which internal phenomena susceptible of self-observation prevail, it seeks to extrapolate the affective features of the linguistic attitudes of the population studied through a matched-guise and a questionnaire, instruments that inquire perceptions regarding five dialects very frequent used in the university. The results show different assessments of the dialects and an opinion on the Bogota accent as central, prestigious and standard, strongly associated with forms of academic orality.